The Effect of Particle Size on the Interpretation of Pore Structure of Shale by N2 Adsorption. (24th April 2021) - Lyu, Chengfu; Zhou, Xinmao; Lu, Xuesong; Zhang, Ying; Li, Chao; Zhou, Qianshan; Sun, Zhaotong; Chen, Guojun
Abstract : Gas adsorption experiments are becoming one of the most common methods to quantify and analyze the pore structures of shale samples in the petroleum industry. In this regard, particle size of the specimen plays an important role in the results that could ultimately affect the pore structure interpretation. Hence, in this study, five shale samples at different thermal maturity levels are picked, and all are crushed into different groups of particle sizes: less than 40 mesh (<375  μ m), less than 60 mesh (<250  μ m), less than 80 mesh (<187.5  μ m), and less than 100 mesh (<150  μ m). Next, N2 adsorption is used to characterize the pore structures of the samples within different particle sizes. Furthermore, to interpret the data, several attributes such as the pore volume, surface area, fractal dimension (from the fractal analysis), and heterogeneity index (from the multifractal analysis), are studied and compared between the samples and particle size intervals to provide us with the effect that particle size could have on the pore structure analysis. The results showed that as the particle size varies, the pore structures of the shale samples could get affected. Based on the comparison of the results, it is recommended that a suitable particle size for the shale pore structure characterization in N2 adsorption experiments should be less than 60 mesh (<250  μ m).